استغلال المال السياسي في وسائل القانون التجاري - كاظم المولى, نداء (revue mofakir, 2018)
Some new terms have been introduced lately which create legal issues that need to be studied as they directly affect the legal system at different economical, political and social levels. Political money is one of these terms. It is that money which is found in public activities, voluntary organizations, and non-governmental associations. Chapter one deals with the nature of political money; its definitions, characteristics, and legal makeup, whereas chapter two deals with the most validated commercial law means of exploiting political money including those occur in business and store together with the suitable commercial contracts and its effect on the commercial papers. The study ends with a conclusion which clarifies the results of the study.